Fintech and Artificial Intelligence: a strategic alliance in the financing of third sector entities - Gómez Álvarez, Juan Jesús (REVESCO. Revista de Estudios Cooperativos, 2023)
Third sector organizations are structurally highly dependent on public subsidies and grants. This paper analyses a complementary means of financing them through the main forms of Fintech, including crowdfunding, blockchain technology and the use of Artificial Intelligence (AI) applied to this field. In parallel, some of the specific cases that are having a greater impact in the area of technological innovation are examined, including the Social Exchange and the Crowcoop project in crowdfunding, the complementary social cryptocurrencies, such as the Par Coin, the ILLA Coin and the G1 Free Coin based on Blockchain technology and, finally, the Ulysses, Dataro or Salesforce programmes in the area of AI. In recent times we are witnessing the implementation of different regulatory frameworks that will provide instrumentality to the new financing models. In the European Union, we have the Action Plan for the Social Economy, the Markets in Cryptoassets Regulation (MiCA) and the proposal for a European Regulation establishing harmonized rules in the field of Artificial Intelligence (AI). For their part, in Spain, laws on the digital transformation of the financial system and on the creation and growth of companies have encouraged the integration and development of new digital business models. In the European Union we have the Action Plan for the Social Economy, the Markets in Cryptoassets Regulation (MiCA) and the proposal for a European Regulation establishing harmonized rules on Artificial Intelligence (AI). For their part, in Spain, laws on the digital transformation of the financial system and on the creation and growth of companies have encouraged the integration and development of new digital business models. All of this, together with the widespread access to and use of technology, provides the third sector with the necessary tools for the implementation of Fintech, offering greater possibilities for sustainability and financial independence.
Keywords: Third sector; Fintech; Crowdfunding; Blockchain; Artificial Intelligence